Model Predictive Control Untuk Kendali Konverter Buck-Boost - Rehiara, Adelhard Beni; Yanty Rumengan (ReTII, 2020)
The process of converting DC electric current is not like converting an AC electric current. In the process of converting DC current, a DC-DC converter is needed. The buck-boost converter is a type of DC-DC converter that can either increase or decrease the output voltage simultaneously. MPC has interested mankind to be developed, in order to get a reliable type of controller. In this research, MPC has been developed utilizing the Laguerre function which is used as a buck-boost converter controller with the network length N = 4, the scale factor a= 0,7, the prediction horizon Np = 20 and the control horizon Nc = 2. Simulations were carried out with variations in load resistance between 10-40 â„¦ and setpoint alteration among 10-70 V. The simulation results show that MPC based on the Laguerre function can control the buck-boost converter system properly without overshoot with peak time and steady state about 0.001 second.